Adult-Onset Autoimmune Enteropathy in an European Tertiary Referral Center. Issue 8 (1st August 2021) - van Wanrooij, Roy L.J.; Neefjes-Borst, E. Andra; Bontkes, Hetty J.; Schreurs, Marco W.J.; Langerak, Anton W.; Mulder, Chris J.J.; Bouma, Gerd
Abstract : INTRODUCTION: Adult-onset autoimmune enteropathy (AIE) is a rare cause of severe chronic diarrhea because of small intestinal villous atrophy. We report on patients with adult-onset AIE in an European referral center. METHODS: Retrospective study including patients diagnosed with AIE in the Amsterdam UMC, location VUmc, between January 2003 and December 2019. Clinical, serological, and histological features and response to treatment were reported. The specificity of antienterocyte antibodies (AEA) was evaluated by examining the prevalence of AEA in (i) controls (n = 30) and in patients with (ii) AIE (n = 13), (iii) celiac disease (CD, n = 52), (iv) refractory celiac disease type 2 (n = 18), and (v) enteropathy-associated T-cell lymphoma (EATL, n = 10). RESULTS: Thirteen AIE patients were included, 8 women (62%), median age of 52 years (range 23–73), and 6 (46%) with an autoimmune disease. AEA were observed in 11 cases (85%), but were also found in CD (7.7%), refractory celiac disease type 2 (16.7%), and EATL (20%). Ten patients (77%) were human leukocyte antigen DQ2.5 heterozygous. Total parenteral nutrition was required in 8 cases (62%). Steroids induced clinical remission in 8 cases (62%). Step-up therapy with rituximab, cyclosporine, infliximab, and cladribine in steroid-refractory patients was only moderately effective. Four patients died (31%), but 4 (31%) others are in long-term drug-free remission after receiving immunosuppressive treatment, including 1 patient who underwent autologous stem cell transplantation. DISCUSSION: Adult-onset AIE is a rare but severe enteropathy that occurs in patients susceptible for autoimmune disease. Four patients (31%) died secondary to therapy-refractory malabsorption, while immunosuppressive therapy leads to a long-lasting drug-free remission in one-third of patients.